REKONSTRUKSI SISTEM KAPITAL DAN STRATEGI PENGUASAAN TUBUH MELALUI TEKNOLOGI - Muhammad Akbar Setiadi; Rikrik Kusmara; Deden Hendan Durahman (ATRAT: Jurnal Seni Rupa, 2018)
Gaze means that someone is looking at an object. It allows you to be a gaze so that you can see or display yourself. In the gaze, it also shows that the gaze is the owner that can be said to be the ruler. The presence of a camera as an object recording tool places it at the voyeurism stage that recording activities are actions without intervention, observing unnoticed. Someone who is behind the camera lens has full power on what he records in front of the camera lens, powers can also be used by image observers on the screen. At this stage the camera can represent gaze control. Users are also able to control the framing of visual representations on the screen that are being gazed at by the audience, the observer is made to believe what is presented through the presentation screen frame boundaries even if what is displayed is not entirely real, even through the latest video technology which is supposed to represent reality and similarities. Men’s activities as a gaze on women’s bodies as objects, in various interests of corporate media, women’s bodies are presented as objects of spectacle that are both pleasurable and painful for the audience (especially men), the audience becomes the controller of what he looks at, but he does not realize that besides the presence the body of the viewer, which is controlled by a woman’s gaze on the screen, is under the power of the screen she is staring at.Keywords: Gaze, Power, Video, Camera, Voyeurism________________________________________________________________ Gaze berarti seseorang sedang melihat, membiarkan dirinya menjadi tatapan agar dilihat atau menampilkan dirinya. Dalam gaze, si penatap merupakan penoton yang memiliki kuasa. Kehadiran kamera sebagai alat (tools) perekam objek menempatkannya pada tahap voyeurisme bahwa aktifitas merekam adalah aksi tanpa intervensi, mengamati tanpa diketahui. Seseorang yang berada di balik lensa kamera memiliki kekuasaan penuh pada apa yang ia rekam di depan lensa kamera, kekuasaan dapat pula di gunakan oleh pengamat citraan pada layar tersebut. Pada tahap ini kamera dapat merepresentasikan pengendalian tatapan. Penggunanya mampu mengendalikan pula pembingkaian representasi visual pada layar yang sedang ditatap oleh pengamatnya (audience), pengamat dibuat untuk mempercayai apa yang disajikan melalui batasan bingkai layar presentasi sekalipun apa yang ditampilan tidak sepenuhnya nyata, sekalipun melalui teknologi video terkini yang disinyalir mampu merepresentasikan kenyataan dan kemiripan yang sebenarnya. Aktifitas pria sebagai penatap atas tubuh perempuan sebagai objek, dalam berbagai kepentingan media korporat, tubuh perempuan disajikan sebagai objek tontonan yang begitu nikmat sekaligus menyakitkan bagi penontonnya (khususnya pria), penonton menjadi pengendali dari apa yang dia tatap, namun ia tidak menyadari bahwa selain kehadiran tubuh penonton yang dikendalikan oleh tatapan perempuan pada layar, dirinya pun sedang barada di bawah kekuasaan layar yang ia tatap.Kata Kunci: Gaze, Kekuasaan, Video, Kamera, Voyeurisme